EXPERIMENTAL INVESTIGATION AND MECHANISM ANALYSIS: EFFECT OF CONCENTRATION AND TEMPERATURE ON THE VISCOSITY OF NOVEL MWCNT-MUSTARD OIL NANOFLUID - V., Vignesh; S., Vijayan; G., Selvakumar (Journal of the Chilean Chemical Society, 2020)
The bio-oils as alternative lubricating fluid is a potential solution for the automotive and industrial mechanical systems. The development of novel renewable and non-toxic bio-lubricants with better lubricating distinctiveness will strengthen the economy of farmers in the agricultural based countries. In the present study, different weight fractions of MWCNT-Mustard oil nanofluids are formulated and their possible effects on the dispersion stability and dynamic viscosity are experimentally investigated over the temperatures ranging from 40 to 100°C. It is observed that the dynamic viscosity and viscosity index of nanofluids were declined with temperature raise, while, it exponentially increased with the raise of MWCNT concentration. The maximum viscosity enhancement of 101.3% is achieved in comparison to the base fluid at 100ºC. Further, the dynamic viscosity of nanofluids is compared with different classical semi-empirical correlations, however, the remarkable conformities were observed from multilayer feed forward Perceptron (MLP) of artificial neural network (ANN).